Simple three-dimensional craniofacial surface measurement - Shuen Chuan, Tan (Penerbit UTM, 2007)
Craniofacial pre-operative planning and post-operative prediction applications are gaining more and more attention since the introduction of computer-aided devices in medical realm. This is due to that applications associated with this field are crucial for many tasks in diagnosis and treatment planning, as for example in the pre-operative and post-operative of craniofacial surgery. Currently, it is common practice in radiology to use 2D measurement tools for the definition of distance, diameters, arcas or angles in planar slices of radiological data. This, however, gives only rough estimation for spatial measurements such as the extent of a 3D object. In particular, the volume of 3D objects can only be estimated roughly. Therefore, tools are required that integrate measurements in 3D visualizations. The development of measurement tools to be used in the context of complex 3D visualization is difficult because the user has to be provided with enough depth cues to access the position and orientation of such a measurement tool. A simple transition of existing line-based 2D measurement tools into 3D is not sufficient.